EQ-5D-5L questionnaire as suitable assessment of quality of life after epiduroscopy : Multicenter randomized double-blind pilot study - Rapčan, Róbert; Kočan, Ladislav; Witkovsky, Viktor; Mláka, Juraj; Griger, Martin; Burianek, Miroslav; Rapčanová, Simona; Hammond, Anthony; Poliak, Ľubomír; Tirpák, Róbert; Šimonová, Jana; Sabol, František; et al. (Wiener klinische Wochenschrift, 2020)
BACKGROUND: Epiduroscopy is a well-established diagnostic and to certain level therapeutic tool in complex situations, where conventional methods such as magnetic resonance imaging (MRI) lack power or resolution to detect pathological changes. Such a situation is primarily failed back surgery syndrome (FBSS) but also radicular pain without surgery. The aim of this study was to determine the effectiveness of epiduroscopic treatment in patients with FBSS. METHODS: A total of 79 patients with FBSS were randomized into 2 groups. The first group underwent epiduroscopy and received mechanical lysis of adhesions only, the second group received also medication into the epidural space (methylprednisolone and hyaluronidase). Patients were subsequently followed for 12 months, with evaluation also after 6 months post-epiduroscopy. Patients were checked in terms of mobility, self-care, usual activities, pain/discomfort and anxiety/depression as defined in the 5‑dimensional EQ-5D-5L questionnaire and to asses suitability of this questionnaire in chronic pain states. Data were collected using EQ-5D-5L questionnaire and also quality of life (QoL) questionnaire. RESULTS: In the terms of ability to walk (dimension mobility) and also ability to do housework, study or leisure activities (dimension usual activity) patients improved in both groups after 6 and 12 months after epiduroscopy. In pain dimension there was improvement mainly after 6 months which correlated also with self-care dimension and quality of life self-assessment. Results in anxiety/depression dimension were mixed. CONCLUSION: Epiduroscopy appears to be a beneficial procedure for both patient groups, especially after 6 months, with some benefit remaining after 12 months. The EQ-5D-5L questionnaire seems to be a suitable and comprehensive way to assess patient health in chronic pain states.
Keywords: dvojitá slepá metoda; Psychometrics; deprese; Double-Blind Method; psychometrie; lidé; Depression; průzkumy a dotazníky; EQ-5D-5L questionnaire; kvalita života; Humans; Failed back surgery syndrome; Back pain; Surveys and Questionnaires; pilotní projekty; Pilot Projects; Quality of Life; Epiduroscopy; Hyaluronidase